Applying mulch and manure in smallholder cropping systems: challenges, realities, limitations, and opportunities - Setsoafia, Eugene Dela; Maat, Harro; El Gharous, Mohamed; Bindraban, Prem; Freeman, Comfort; Struik, Paul C. (Frontiers in Sustainable Food Systems, 2025)
IntroductionSoil fertility plays an important role in crop production. However, continuous cropping with minimal fertilizer application has resulted in declining soil fertility and correspondingly low crop yields in smallholder cropping systems. The decline in soil fertility can be partially mitigated by applying local, organic sources of nutrients.MethodsThrough focus group discussions, this paper explored soil fertility management, focusing on mulch and manure, bringing fresh attention to practical, farmer-led solutions. This study links agronomic practices with the Social Practice theory to show farming as socially embedded rather than purely technical.ResultsWe found that the use of mulch was primarily limited to specific crops—pepper, tomato, garden egg, and yam, planted on less than 0.4 ha of farm field. Manure was applied preferably to maize fields due to the high nutrient requirement of maize and its important role as a staple. Farmers’ understanding of mulch and manure applications reflected a blend of traditional knowledge and scientifically recognized benefits.DiscussionThese practices were valued for their role in protecting perishable crops from pests and drought-related stress and providing a sustained nutrient supply, offering a more affordable alternative to chemical fertilizers. Farmers demonstrated varying levels of competence in their assessment of the quantity of manure required for maize crop production and the timing and mode of application of mulch and manure. The emergence of weeds in fields treated with manure and the lack of competence to manage these weeds, however, require skills and competency development to enable the sustained application of manure.